Retroperitoneal Leiomyosarcoma Mimicking Acute Appendicitis: Laparoscopic Management - Agresta, Ferdinando (Society of Laparoendoscopic Surgeons, 2003)
BACKGROUND: Retroperitoneal leiomyosarcomas (RLMS) are a challenging clinical entity. The vast majority of patients are operated on when tumors are advanced. We report herein a case of RLMS, mimicking acute appendiceal disease and treated successfully via laparoscopy. METHODS: A 37-year-old woman, para 1, was admitted to our department for right lower quadrant abdominal pain, fever, and leukocytosis. She had no changes in gastrointestinal and urologic function. A physical examination revealed the presence of abdominal guarding, rebound, and a tender mass in the right lower quadrant. The abdominal ultrasound showed an inhomogeneous ovoid mass (6 cm in diameter) located below the cecum, with no definite margins, and consistent with an appendiceal abscess. The patient was referred for laparoscopy. The procedure was performed with the aid of 3 ports: a 12-mm trocar in the umbilicus (open technique), a 10-mm trocar in the left iliac fossa, and a 5-mm one in the suprapubic space. On inspection of the abdominal cavity, a retroperitoneal 6-cm mass was immediately found below the cecum and the appendix. Neither intraperitoneal seeding nor suspected lymph nodes were present. After dissection of the parietal peritoneum, the mass appeared to be encapsulated and well demarcated from all surrounding structures. It was eventually dissected and removed via a plastic bag. A standard appendectomy was also performed. The postoperative course was uneventful, and the patient was discharged on the 3rd day. The histology analysis of the resected specimen showed a totally excised G2 leiomyosarcoma. The appendix had no signs of inflammation. Postoperatively, the patient underwent a total-body CT-scan, which had no signs of residual or distant disease. No adjuvant therapy was necessary. At an 18-month follow-up, the patient was doing well and was disease free. CONCLUSIONS: Surgery represents the main therapeutic option for resectable RLMS. Laparoscopy is a useful diagnostic tool that allows safe resection of incidentally discovered, small and well encapsulated RLMS.